Comparison of long-term outcomes between endoscopic band ligation and endoscopic clipping for colonic diverticular hemorrhage - Nakano, Kaoru; Ishii, Naoki; Ikeya, Takashi; Ego, Mai; Shimamura, Yuto; Takagi, Koichi; Nakamura, Kenji; Fukuda, Katsuyuki; Fujita, Yoshiyuki (Endoscopy International Open, 2015)
Background and study aims: Long-term outcomes of endoscopic band ligation (EBL) for colonic diverticular hemorrhage have not been reported to date. The aim of this study was to determine the long-term outcomes of EBL and to retrospectively compare them with those of endoscopic clipping (EC) in the treatment of colonic diverticular hemorrhage.Patients and methods: The study included patients with colonic diverticular hemorrhage who were treated with EBL or EC from January 2004 to November 2014 and followed up more than 1 year (61 patients in the EBL group and 39 patients in the EC group). Time-to-event analysis of rebleeding was performed with the Kaplan-Meier method. A follow-up colonoscopy was performed to confirm the disappearance of the banded diverticula in the EBL group.Results: Rebleeding occurred in 21 patients in the EBL group and in 26 patients in the EC group. The cumulative incidence of rebleeding at 1, 12, 24, and 36 months after first treatments was 14 %, 23 %, 26 %, and 41 % in the EBL group and 38 %, 49 %, 59 %, and 68 % in the EC group, respectively. Time-to-event analysis revealed statistically significant data (Log-rank test, P = 0.0036). Scar formation with fold convergence at the previously banded site was observed in 11 of 24 patients who underwent follow-up colonoscopy (46 %). However, late rebleeding (rebleeding more than 30 days after EBL) occurred in five of these 11 cases.Conclusions: EBL was superior to EC in the treatment of colonic diverticular hemorrhage. However, the risk of rebleeding was not avoided even after the diverticula had been resolved using EBL.